Incorporating Multimedia in Social Studies Instruction: Does it Improve Students’ Performance, Interest, and Instructional Effectiveness Attitude? - Brown, Scott W.; Ioannou, Andri (My University, 2007)
This study investigates whether using multimedia-based instructional material in social studies class may enhance students’ learning about world issues, elicit their interest in social studies, and generate positive attitudes toward instructional effectiveness, greater than text -based material. The investigation was set in the GlobalEd Project, a web-based international negotiations simulation embedded in the middle school social studies curriculum. The study employed an experimental design with a multimedia group (MG, experimental condition) and a text group (TG, comparison condition). Results provided no direct evidence that multimedia is more effective than text, with regards to our outcome measures. However, although not statistically significantly, students in MG showed larger gains in knowledge and interest as a result of the intervention, as well as more positive instructional effectiveness attitudes. In addition, students in MG used the instructional material more extensively than students in TG.
Keywords: GlobalEd Project